PERANCANGAN APLIKASI E-LIBRARY BERBASIS WEB PADA SMK NEGERI 2 PAGAR ALAM - Jaya, Heru Sipta; Agustin, Ayu Tri; Humaidah, Fitria; Prambayun, Arif (Universitas Lembah Dempo, 2021)
The development of information technology today has become a necessity for its users. library services that exist at SMK Negeri 2 Pagar Alam are still done manually. Making it possible during the process there was an error in recording, less accurate reports made, and delays in finding the data needed. In this discussion, the application of information technology discussed is shown in the field of education at SMK Negeri 2 Pagar Alam to design e-library applications (electronic library). This e-library application is designed using the PHP, javascript, HTML programming language, the research methods used in making this web-based e-library application are observation, interviews, and literature study. System development method using the waterfall method. This application will be accessed via the intranet (local network) at SMK Negeri 2 Pagar Alam. This application provides solutions in book management such as: searching for books, adding books, knowing the number of books, borrowing books, and being able to add library members. and all that can be accessed by the admin as a librarian in carrying out full management access rights and users as library members who can search for books or borrow books.